2020
DOI: 10.1080/19490976.2020.1747329
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbial profile is associated with abnormal metabolism activity of Autism Spectrum Disorder

Abstract: Autism Spectrum Disorder (ASD) is a severe neurodevelopmental disorder. To enhance the understanding of the gut microbiota structure in ASD children at different ages as well as the relationship between gut microbiota and fecal metabolites, we first used the 16S rRNA sequencing to evaluate the gut microbial population in a cohort of 143 children aged 2-13 years old. We found that the α-diversity of ASD group showed no significant change with age, while the TD group showed increased α-diversity with age, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
211
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(261 citation statements)
references
References 82 publications
(87 reference statements)
18
211
3
1
Order By: Relevance
“…Compared to targeted sequencing of 16 S ribosomal DNA (rDNA), which only presents species profiles, shotgun sequencing is more informative, as it provides comprehensive information for the inference of concrete metabolic pathways and physiological functions of the microbiome ( 11 ). Although few studies of shotgun-based metagenome analysis have been reported for the ASD intestinal microbiome ( 12 , 13 ), obstacles remain because of high interindividual diversity, which is influenced by a wide range of factors such as genetics, age, diet, and healthy conditions ( 14 ). The individual diversity is often so great and difficult to control that it even overwhelms disease-associated alterations and profoundly affects the identification of disease-associated microbiome features.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to targeted sequencing of 16 S ribosomal DNA (rDNA), which only presents species profiles, shotgun sequencing is more informative, as it provides comprehensive information for the inference of concrete metabolic pathways and physiological functions of the microbiome ( 11 ). Although few studies of shotgun-based metagenome analysis have been reported for the ASD intestinal microbiome ( 12 , 13 ), obstacles remain because of high interindividual diversity, which is influenced by a wide range of factors such as genetics, age, diet, and healthy conditions ( 14 ). The individual diversity is often so great and difficult to control that it even overwhelms disease-associated alterations and profoundly affects the identification of disease-associated microbiome features.…”
Section: Introductionmentioning
confidence: 99%
“…MD Angelis et al [12] found higher amounts of tryptophan and 3methylindole in the feces of children with ASD. Dan Z et al [38] also reported abnormal metabolism of tryptophan in the gut of ASD children. An experiment in mice model of autism found a decrease of serotonin in intestine mucosal [39].…”
Section: Discussionmentioning
confidence: 97%
“…The differences between any two network structures were compared by node closeness centralities and shared correlations. 42 The shared correlations between two groups were defined the edges with the same nodes in two co-occurrence networks. Closeness centralities of the nodes was calculated by Cytoscape (v3.6.1) to measure node centralities in each network.…”
Section: Co-occurrence Network Analysismentioning
confidence: 99%